Higher spin swampland conjecture for massive AdS$_{3}$ gravity - Rajae Sammani, El Hassan Saidi (SciPost Physics)
In this paper, we show that a possible version of the swampland weak gravity conjecture for higher spin (HS) massive topological AdS$_{3}$ gravity can be expressed in terms of mass M$_{\mathrm{hs}}$, charge Q$_{\mathrm{hs}}$ and coupling constant ${\large g}_{\mathrm{hs}}$ of 3D gravity coupled to higher spin fields as M$_{\mathrm{hs}}≤ \sqrt{2}$Q$_{\mathrm{hs}}{\large g}_{\mathrm{hs}}M_{\mathrm{Pl}}$. The higher spin charge is given by the $SO(1,2)$ quadratic Casimir Q$_{\mathrm{hs}}^{2}=s\left( s-1\right) $ and the HS coupling constant by ${\large g}_{\mathrm{hs}}^{2}=2/\left( M_{\mathrm{Pl}}^{2}l_{\mathrm{AdS}_{3}}^{2}\right) $ while the mass expressed like $\left( l_{\mathrm{AdS}_{3}}\text{M}_{\mathrm{hs}}\right) ^{2}$ is defined as $\left( 1+\mathrm{\mu }l_{\mathrm{AdS}_{3}}\right) ^{2}s\left( s-1\right) +\left[1-\left( \mathrm{\mu }l_{\mathrm{AdS}_{3}}\right) ^{2}\left( s-1\right) \right]$.